Benefits of having friends in older ages: differential effects of informal social activities on well-being in middle-aged and older adults - Huxhold, Oliver; Gabrian, Martina; Schüz, Benjamin Ernst Christoph (The journals of gerontology. Series B, Psychological sciences, social sciences, 2014)
Abstract: Objectives. It has been considered a fact that informal social activities promote well-being in old age, irrespective of whether they are performed with friends or family members. Fundamental differences in the relationship quality between family members (obligatory) and friends (voluntary), however, suggest differential effects on well-being. Further, age-related changes in networks suggest age-differential effects of social activities on well-being, as older adults cease emotionally detrimental relationships.